CIRCULAR ECONOMY: INNOVATIVE AND SUSTAINABLE BUSINESS MODELS IN THE FASHION INDUSTRY - GARAFONOVA, OLGA; VIETROVA, DARIA; MARHASOVA, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Promoting sustainable fashion within the circular economy is an important contemporary topic. Experts in design, consumption, business and industry explain how to approach circularity in fashion production and consumption in different ways. Increasingly, new and existing companies are looking for ways to thrive in a competitive environment through innovative business models, taking into account public opinion and avoiding actions that harm the planet. Trends such as the circular economy, fair trade, and sharing policies are among the many new approaches to business that address these issues, but there is still a gap between the theory that argues for levels of environmental and social sustainability and the implementation of these strategies in practice. That is why the study of the current state of the circular economy is relevant.This article presents the principles of the circular economy in terms of fashion. The key aspects of the integration of sustainable development in the fashion industry are considered. Different approaches of new business models for the circularity of the economy are highlighted. The main directions of implementation of sustainability strategies due to business transformation are identified, which requires the construction of a new level of the system and radical innovations.
Keywords: circular economy; sustainable business models; innovations; strategic management; product life cycle; brand management; competitive strategy; slow fashion